Web Online: Empowering the Student’s Pronunciation - Astuti, Reny Windi; Mariana, Tety (JET ADI BUANA, 2016)
As an important component in the context of teachingEFL, pronunciation is considered as one of the core language partsin the achievement of successful learning English. Pronunciationplays an important role in conducting the students how to speaksome English words appropriately. Some students are ofteninterfered by English pronunciation. They are difficult to definehow to pronounce English words well. On the other hand, bypronouncing English words accurately, the students can expandtheir communication efficiency. Helping the students hear andproduce English sounds is one of main tasks of English teachers todevelop the students’ English competence.This research aimed at investigating how to teach Englishpronunciation through Web Online. The research was conducted tothe eleventh graders of vocational high school in Academic Year of2015/2016. This research was Classroom Action Research (CAR).The implementation of the technique was carried out in sixmeetings in two cycles (each cycle was three meetings). The resultsof the research showed that there were: (1) improvement of thestudents’ mean score in pronunciation test. It indicated that WebOnline brought positive improvement on students’ pronunciation.(2) Improvement of the students’ involvement during the processof learning English. By analyzing the data of questionnaire andobservation checklist, the researchers found that most of thestudents had positive response in learning pronunciation. Derivedfrom the findings, it can be concluded that Web Online hasimproved the students’ pronunciation in the process of learningEnglish. It theoretically and practically helps students pronounceEnglish words better.